Deteksi Dini Loyalitas: Pelajaran Empiris dari Daerah Obyek Wisata Lawang Sewu Semarang - Aprih Santoso (Badan Perencanaan Pembangunan Daerah Kota Semarang, 2023)
The research aims to analyze the impact of service quality and satisfaction on tourist loyalty in the Lawang Sewu Tourism Area, Semarang. The sample taken in this research was carried out by a population of tourists who went on tour in the Lawang Sewu Tourism Object Area, Semarang, where the number is unknown. The sample was taken using purposive sampling and amounted to 100 people. The analysis method is multiple linear regression. The analysis method uses linear regression multiple regression. The results of the research show that service quality has an impact on tourist loyalty, the service quality provided by the management of the Lawang Sewu Tourist Attraction Area, Semarang City, with operational service speed so that the better the service quality, the more loyalty will result. Satisfaction has an impact on tourist loyalty. Satisfaction is given by the management of the Lawang Sewu Tourism Object Area, Semarang City, which is very comfortable, the better tourist satisfaction will increase tourist loyalty.